Impact of a Booklet about Diabetes Genetic Susceptibility and Its Prevention on Attitudes towards Prevention and Perceived Behavioral Change in Patients with Type 2 Diabetes and Their Offspring - Nishigaki, Masakazu (SAGE-Hindawi Access to Research, 2011)
Background. Offspring of type 2 diabetic patients are at a high risk of type 2 diabetes. Information on diabetes genetic susceptibility and prevention should be supplied to the offspring. Methods. A six-page booklet on diabetes genetic susceptibility and prevention was distributed to 173 patients who ere ordered to hand it to their offspring. The patients answered a self-administered questionnaire on booklet delivery and attitudinal and behavioral changes toward diabetes and its prevention in themselves and their offspring. Results. Valid responses were obtained from 130 patients. Forty-nine patients had actually handed the booklet. Booklet induces more relief than anxiety. From the patient's view, favorable attitudinal and/or behavioral changes occurred in more than half of the offspring who were delivered the booklet. Conclusion. The booklet worked effectively on attitudes and behaviors toward diabetes and its prevention both in patients and their offspring. However, the effectiveness of patients as information deliverers was limited.